Automatized Multi-Electrode Voltage Map Measurement of Active Points on Skin - Marek Kukucka; Zuzana Krajcuskova (Communications - Scientific letters of the University of Zilina, 2011)
Our contribution deals with the human skin voltage chart measurement. We have concentrated our effort on finding and following the measurement of active points on different parts of the skin's surface, to acknowledge their existence and position through a measuring process. The human skin has a certain impedance or resistance – it can be easily described and simulated using a substitute electric circuit. But the skin also contains parts with measurably lower impedance and different electric properties – we can show them clearly by measurement of voltage chart.